PENGARUH PENERAPAN LKPD BERORIENTASI PENDEKATAN BRAIN BASED LEARNING (BBL) TERHADAP PENCAPAIAN KOMPETENSI IPA PESERTA DIDIK KELAS VIII SMP NEGERI 1 KOTA SOLOK - Sri Ayu Wahyuni; Mahrizal Mahrizal; Letmi Dwiridal (Universitas Negeri Padang, 2016)
One of the factors that lead to the low science competencies of students is the use of Student Worksheet (LKPD) that do not support the achievement of competencies, from the aspect of spiritual, attitudes, knowledge, and skills. The purpose of this study is to determine the application effect of LKPD oriented with Brain Based Learning (BBL) approach to the achievement of science competency of the VIII grade students in SMP Negeri 1 Solok. This study is a Quasy Experimental Research with a randomized control group only design. The study population was all students of VIII grade in SMP Negeri 1 Solok listed in the Academic Year 2015/2016. Sampling was done by purposive sampling technique. Data from this study include the achievement of spiritual attitudes, social attitudes, knowledge, and skills competencies. The research instrument is observation sheet for spiritual and social attitudes competence, written test for knowledge competence, and performance assessment for competence skills. Data were analyzed using Chi Square test at the real level of 0.05 for the spiritual aspects of attitudes, social, knowledge, and skills. The result of data analysis of student competencies in spiritual attitudes, social attitudes, knowledge, and performance skills competencies of the experimental class are 78,07; 76,55; 76,32; and 79,70; while the control class are 76,50; 74,40; 71,94; and 77,30. The data showed that the experimental group had a higher level of competence than the control class. Chi Square test results obtained contingency coefficient C for competence spiritual attitudes, social, knowledge, and skills of each 0,062, 0,287, 0,292 dan 0,031. From these results it can be argued that the application effect of LKPD oriented with Brain Based Learning (BBL) approach has significant impact on the Achievement of Science Competency of the VIII Grade Students in SMP Negeri 1 Solok on social attitudes, knowledge, and skills competencies. While on the spiritual attitude competence, the LKPD oriented with Brain Based Learning (BBL) approach is not optimal to give effect to the achievement of Science Competency of the VIII Grade Students in SMP Negeri 1 Solok.